HASIL PERBANDINGAN RETURN TRANSAKSI INDEKS GOLD PADA INDIKATOR MOVING AVERAGE, STOCHASTIC OSCILLATOR DAN RELATIVE STRENGTH INDEX PADA TAHUN 2014-2016 - Kevin Natanael (Universitas Katolik Widya Karya Malang, 2020)
This study aims to analyze and compare the returntransactions in index gold using technical analysis which theindicators are Moving Average, Stochastic Oscillator andRelative Strength Index also the combination of that threeindicators in the year of 2014-2016. The simulation oftrading which based on the trading plans which has beenmade for both of each indicators and the combination ofindicators. The trading simulation in this research is usingFBS trader software. The trading simulation’s results showsthat Moving Average indicator reaches the highest returnwhich is 134578 pips. Stochastic Oscillator indicator reachesthe profit 2505 pips and Relative Strength Index reaches lossof 420 pips. On other hand, the combination of the indicatorsonly reaches 0 pips because there is no transaction thateligible to both of open position buy and sell. From thesimulation results obtained that indicator which used in theanalysis must be adjusted with the return term.